O2- and N2-broadening parameters in the ν3 and 2ν3-ν3 bands of methyl chloride. (September 2020) - Dridi, N.; Manceron, L.; Fathallah, O. Ben; Rotger, M.; Aroui, H.
Highlights: Systematic measurements of O2 - and N2 -broadening coefficients of ro-vibrational transitions of the ν3 and 2ν3 -ν3 parallel bands of 12 CH3 35 Cl and 12 CH3 37 Cl isotopes have been determined using a high resolution Fourier transform spectrometer. Study of the rotational dependences of large sets of measurements of O2 - and N2 -broadening coefficients has been performed using empirical polynomial expansions. Measured and empirical values of Air-broadenings coefficients are deduced for the ν3 fundamental band and for the 2ν3 -ν3 hot band. Abstract: In this paper, we report high-resolution measurements of oxygen and nitrogen pressure-broadening coefficients for ro-vibrational transitions in the ν3 and 2ν3 -ν3 bands of methyl chloride (CH3 35 Cl and CH3 37 Cl). We present the first high-resolution measurement of oxygen broadening coefficients for the CH3 Cl, along with an extensive determination of the nitrogen broadening coefficients in the ν3 band which complements the measurements made by diode laser spectrometer in previous works. For the 2ν3 -ν3 band, the oxygen and nitrogen broadening coefficients are measured here for the first time. The results have been obtained by analyzing fourteen spectra with a mono-spectrum non-linear least squares fitting of Voigt profile using data recorded at 295 K at the AILES beamline of the SOLEIL Synchrotron facility using a Bruker IF125HR Fourier transform spectrometer. Broadening coefficients of 1793 and 1732 lines in both bands of both isotopes of CH3 Cl for O2 and N2 buffer gases respectively have been retrieved. The rotational dependences of these coefficients have been modeled using an empirical model, which reproduces the measured data with a difference of about 6 %. Using the measured values of O2 - and N2 -broadenings, we derived the Air-broadening coefficients. Finally, comparisons with previous works are performed.